guljahon PRESCHOOL EDUCATION INSTRUCTIONS PRINCIPLES AND INNOVATIVE TECHNOLOGIES OF EDUCATIONAL PROCESSING: PRESCHOOL EDUCATION INSTRUCTIONS PRINCIPLES AND INNOVATIVE TECHNOLOGIES OF EDUCATIONAL PROCESSING - Umrzakova, Guljakhon (Журнал иностранных языков и лингвистики, 2022)
The article deals with the principles of organizing preschool institutions, physical, mental and emotional development of children in preschool institutions, children’s health, the development of creative thinking abilities, the moral and spiritual development of preschool education - preschool educational institution. Based on scientific knowledge, skills and experiences of the teachers.